2019
DOI: 10.1113/jp278173
|View full text |Cite
|
Sign up to set email alerts
|

H‐reflex conditioning during locomotion in people with spinal cord injury

Abstract: r In people or animals with incomplete spinal cord injury (SCI), changing a spinal reflex through an operant conditioning protocol can improve locomotion.r All previous studies conditioned the reflex during steady-state maintenance of a specific posture. By contrast, the present study down-conditioned the reflex during the swing-phase of locomotion in people with hyperreflexia as a result of chronic incomplete SCI. The aim was to modify the functioning of the reflex in a specific phase of a dynamic movement.r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 74 publications
(251 reference statements)
0
36
0
Order By: Relevance
“…In neurologically intact individuals, soleus H-reflex amplitudes are minimal during swing and at heel contact, increase rapidly during stance, and decrease abruptly after toe-off (42,46). SCI disrupts this phase-dependent soleus H-reflex amplitude modulation during walking, varying from relatively normal in some patients to completely absent in others (7,8,12,39,47). The most common change observed after locomotor training is the partial return of soleus H-reflex depression during the swing phase; but extensor motoneuron excitability during the stance phase remains unstable (12,39).…”
Section: Discussionmentioning
confidence: 99%
“…In neurologically intact individuals, soleus H-reflex amplitudes are minimal during swing and at heel contact, increase rapidly during stance, and decrease abruptly after toe-off (42,46). SCI disrupts this phase-dependent soleus H-reflex amplitude modulation during walking, varying from relatively normal in some patients to completely absent in others (7,8,12,39,47). The most common change observed after locomotor training is the partial return of soleus H-reflex depression during the swing phase; but extensor motoneuron excitability during the stance phase remains unstable (12,39).…”
Section: Discussionmentioning
confidence: 99%
“…Note that a simple contextualization can drive motivation if the participant sees how the task can positively impact their life outside of the research lab, yet these person-centered outcomes are rarely if ever included in research protocols (Winstein, 2018). To further support our argument, recent studies have shown that motivation can mediate long-lasting neural plasticity: for example, operant conditioning protocols use a reward-based approach to downregulate plantarflexor muscle H-reflex through brain and spinal cord plasticity (Wolpaw et al, 1986;Thompson and Wolpaw, 2014;Chen et al, 2017), which can restore preinjury reflex excitability and invoke positive changes in walking function (Thompson et al, 2013;Thompson and Wolpaw, 2019). Therefore, the contextualization process establishes meaningful goals linked to the research task being used to promote recovery through fundamental learning-based processes, supported by brain and spinal cord plasticity (Tsay and Winstein, 2020).…”
Section: Consideration 3: Secondary Measures Are Needed To Track and Mitigate Emergence Of Compensatory Behaviors During Interventionsmentioning
confidence: 87%
“…Among the major descending pathways, the corticospinal tract is the only pathway essential for conditioning-induced plasticity ( 97 ). Thus, when the corticospinal tract and its plasticity are preserved at least partially, the targeted change can be induced through conditioning ( 98 ), which then changes how that reflex pathway functions in complex motion such as locomotion ( 80 , 92 , 99 ). These provide the foundation for currently emerging clinical applications of MEP operant conditioning.…”
Section: Operant Conditioning Of Emg-evoked Potentialsmentioning
confidence: 99%
“…In addition to MEP conditioning protocols, several reflex conditioning protocols are currently being developed. To date, two protocols have been systematically tested in people with or without CNS damage: the soleus short-latency stretch reflex (known as M1 response) conditioning, using mechanical joint perturbation ( 135 ), and the soleus H-reflex conditioning, which uses electrical stimulation of the tibial nerve ( 92 , 99 , 102 , 136 ). With both stretch and H-reflex conditioning protocols, the person learns to increase or decrease the target reflex size over 24–30 conditioning sessions.…”
Section: Operant Conditioning Of Spinal Reflexesmentioning
confidence: 99%
See 1 more Smart Citation